SLOVAK FOLKLORE AND FOLK CULTURE IN THE CONDITIONS OF EDUCATION OF PUPILS FROM SOCIALLY DISADVANTAGED ENVIRONMENTS IN SLOVAK SCHOOLS - KOPNICKÝ, Miroslav (ГУМАНІТАРНІ СТУДІЇ : ІСТОРІЯ ТА ПЕДАГОГІКА, 2023)
Our country is characterized by its rich cultural past, national traditions and customs, which will be preserved for future generations only if we continue to spread and pass them on in this modern global world. Folklore is an inseparable component of the identity of a given group, it is the bearer of ethnic characteristics, and nowadays it is understood as an irreplaceable part of the intangible cultural heritage. During the preparation and conception of the study, we had the opportunity to look at the richness and diversity of our folk culture, which our country preserves.From a pedagogical point of view, we are offered a lot of topics and inspiration, which we only need to take and adequately give to the youngest generation, as a counterweight of today popular and foreign genres offered by the media. It is only up to us, on our pedagogical approach and feeling, to arouse in students the interest and desire to know and master this kind of art, which has been here since time immemorial, which is closest to our people, is unique and unrepeatable.The study points to the urgency and importance of paying attention to Slovak folklore and the folk culture of our ancestors in the current era, already in education in the pre-primary education of pupils in kindergartens. Appropriate to the age, personality and individual abilities of the children, the teacher knows how to ideally and sensitively integrate nursery rhymes, speech books, folk songs, or music-movement games into educational activities, thereby non-violently and naturally contributing to the preservation and passing on of this heritage. If we want to preserve the cultural past, national traditions and customs of our ancestors for future generations, let's give them enough attention and space, let's teach them with children already in pre-primary education through educational activities and games, otherwise they will forever be forgotten.